Pendampingan Penerapan Miniatur Ekosistem Sebagai Media Pembelajaran Yang Efektif : Pendampingan Penerapan Miniatur Ekosistem Sebagai Media Pembelajaran Yang Efektif - Rina Dian Rahmawati; Sholeh Afyuddin; Muhammad Wahyudi; Afif Kholisun Nashoih; Farid Nasrulloh; Ummi Zulfa Ulya; Lailatul Fikriah; A’idatuzzakiyah A’idatuzzakiyah; Rizky Aditya Nugraha; Lailatul Mathoriyah (LPPM STKIP PGRI Pacitan, 2023)
Mockup media is a type of learning that is made in its original form. The problems faced by partners are that the learning methods used are still fairly classic, there is no supporting media that can be used by educators to maximize the learning process, it is difficult to find direct learning media. This service activity aims to provide assistance as well as to implement miniature ecosystem learning media as an effective learning medium. The method used in carrying out this activity is using Service Learning (SL) which includes lectures and questions and answers. The results show that students are enthusiastic in participating in learning and students are active in learning both asking and answering questions, educators find it easier in the teaching process, and can innovate in making learning media.